STUDI KANDUNGAN MERKURI PADA DAGING BUAH KELAPA DI TEMPAT PENGOLAHAN BIJIH EMAS, DESA TATELU RONDOR KECAMATAN DIMEMBE KABUPATEN MINAHASA - A Tarore, dkk (PPLH-SDA, Lembaga Penelitian Unsrat Manado, 2012)
The use of mercury (Hg) in gold mining activity causes the heavy metal enters into environment. The main pathway of the mercury enter into the environment is due to mercury-containing slurry from rinsing and amalgam processes. Tatelu Rondor Village, Dimembe, Minahasa Regency, has 300 ha of coconut plantation area, which produces about 1800 coconut per area. More than 50% of the gold mining activity is located nearby the coconut plantation area. Present research is conducted in coconut plantation area of Tatelu Rondor Village where since 1998 the gold mining activity occurs. Sampling has done one per two months on coconuts from the mining area and a control location. The sampling area was divided by 5 observed points, such as a center of tailing disposal area, tailing stream area 1 and 2, surrounding area of tailing disposal, and a control location.